Changes in perinatal mental healthcare during the COVID-19 pandemic: a protocol for a collaborative research study between the COST actions RISEUP-PPD and DEVOTION - Emma Motrico; Sandra Nakić Radoš; Ana M Mesquita; Ana Ganho-Avila; Eleni Vousoura; Joan Lalor (BMJ Open)
Introduction Significant changes in routine maternity care have been introduced globally in response to the COVID-19 pandemic to reduce infection risk, but also due to lack of medical facilities, staff shortages and the unpredictable nature of the disease. However, it is yet to be established if specialised perinatal mental health (PMH) services have been similarly affected. As a Task Force in PMH and COVID-19 pandemic within Riseup-PPD COST Action, this study aims to identify changes in PMH practices, policies and protocols during the COVID-19 pandemic in Europe.Methods and analysis An online survey of experts in the PMH who are members of the COST Action ‘Riseup-PPD’ and the COST Action ‘’DEVOTION” across 36 European countries will be conducted. A questionnaire on changes in PMH care practices during the COVID-19 Pandemic will be administered. It consists of open-ended questions, checklists and ratings on a 7-point scale addressing seven domains of interest in terms of PMH: (1) policies, guidelines and protocols; (2) PMH care practices at a national level; (3) evidence of best practice; (4) barriers to usual care; (5) resources invested; (6) benefits of investment in the policies and (7) short-term and long-term expectations of the policies. Data will be collected using Qualtrics. Descriptive statistics will be reported and differences between countries will be examined using the χ2 statistic or Student’s t-test.Ethics and dissemination Ethical approval was obtained from The Ethics Committee for Research in Life and Health Sciences of the University of Minho (Portugal) to undertake an anonymous online survey. The findings will be disseminated to professional audience through peer-review publication and presentations and shared widely with stakeholders, policy-makers and service user groups. A position paper will be developed to influence policy-making at a European level to alleviate the adversities caused by COVID-19.Trial registration number NCT04779775.